The use of the Eurosystem's monetary policy instruments and its monetary policy implementation framework in 2020 and 2021 - Marco Corsi; Yvo Mudde (European Central Bank (ECB), 2022)
The Eurosystem implements its monetary policy through a set of monetary policy instruments (MPIs) that are either part of the standard toolbox or are developed to deal with major economic and financial events with a potential adverse impact on price stability and/or the transmission of monetary policy. In the review period covered by this report (2020-2021), monetary policy action was dominated by the Eurosystem's response to the negative economic effects of the outbreak of the COVID-19 pandemic. Through its action, the Eurosystem continued to expand its balance sheet, in particular by scaling up its outright asset purchases and easing the conditions of its targeted longer-term refinancing operations (TLTROs), complemented by temporary changes in the collateral framework. The accommodative monetary policy stance was preserved by maintaining the key ECB interest rates at record-low levels, reinforced by the ECB's forward guidance on policy rates. This report provides a full overview of the Eurosystem's monetary policy implementation over the years 2020 and 2021.
Keywords: D02; E43; E58; E65; G01; 330; monetary policy implementation; central bank counterparty framework; central bank collateral framework; central bank liquidity management; non-standardmonetary policy measures